PECULIARITIES OF MARKETING MANAGEMENT IN TOURISM BUSINESS (Development Service Industry Management, 2023)
The current state of war in Ukraine is characterized by the sharp decline of the tourism industry in most regions, the curtailment of social development programs in this direction, the loss of positive trends and dynamics of the development of related industries, and the low competitiveness of tourist services. Such conditions require new approaches not only in planning the assortment of services, but also in the formation of new approaches to increasing the efficiency of tourism organizations based on marketing technologies.In modern conditions, a tendency to perceive marketing as a management tool should be formed. Such an approach will allow timely detection of changes in the factors affecting activity (macro- and microenvironment), create effective communications with clients, and strengthen competitive positions on the market.The purpose of the study was to determine the peculiarities of the implementation of marketing management in the tourism business in modern conditions and to identify factors influencing its formation.Each tourist organization has to independently decide on the specifics of its activity, market segments and financial policy. When making strategic decisions, responsible managers of enterprises focus, first of all, on the needs and specifics of the current state of the market.It was found that the work of a tourist firm on the market can be considered in several aspects, including: as the work of state structures, unions, associations in the tourist markets of one or more countries in order to promote their national tourist product and attract tourists to their country or your region; as the work of a tour operator to study the demand for tourist services in order to create a competitive ready-made package of services and ensure its sale; as work on the sale of a ready-made package of tourist services to ensure the successful implementation of tours.Based on the results of the analysis, the main areas of work of the marketing departments of the tourist organization were substantiated. In this regard, their specifics and range of functional responsibilities were investigated.It is noted that when planning marketing activities and when allocating functional responsibilities of the marketing department, trends in the development of tourism in Ukraine should be taken into account. It is important to rely on the relevant security regulations adjusted for martial law.
Keywords: marketing management; tourist business; tourist product; competitive advantage; marketing department functions; management tool